Usability Testing of Web-Based Anti-Doping Monitoring (Haloatlet 1.0) for Physical Impairment Athletes - Fadilah Umar; Deddy Whinata Kardiyanto; Giri Prayogo; Misbah Misbah; Dina Listiani (Journal of Coaching and Sports Science, 2025)
Background: Athletes with disabilities still have limited access to digital anti-doping education, reflecting low digital readiness and unequal access to critical information. This gap increases the risk of unintentional doping, highlighting the urgency of improving digital anti-doping education for this population. Purpose: This study aims to evaluate the usability of the Haloatlet 1.0 monitoring media, which has been developed as part of an effort to prevent doping use among athletes with disabilities, utilizing the Software Development Life Cycle (SDLC) with an iterative model. The research focuses on the usability testing phase of the developed media product. Materials and methods: Data collection involved a sample of 30 athletes selected from 7 different sports. A Likert-scale System Usability Scale (SUS) questionnaire was used as the data collection instrument. The Curved Grading Scale (CGS) was used as a reference to represent the level of usability of Haloatlet 1.0. Results: The usability evaluation of the Haloatlet 1.0 doping prevention monitoring website yielded a SUS score of 81.17 ± 10.74, corresponding to Grade A and falling within the Excellent usability category (top 90–95 percentile). Conclusions: These findings demonstrate that the Haloatlet 1.0 website successfully provides a high level of usability in supporting athletes with physical disabilities in accessing anti-doping information and prevention resources. Effective anti-doping initiatives require continuous collaboration among key stakeholders to ensure clean and fair sports environments. Therefore, the results of this study offer valuable insights for enhancing inclusive and accessible digital anti-doping education policies, particularly for athletes with disabilities who often experience limited access to conventional learning platforms.